E-DOCUMENT INFORMATION SYSTEM ON ACADEMIC QUALITY ASSURANCE AGENCY BASED ON MOBILE DEVICE - Mulyanto, Agus; Bachry, Bobby; Zayyadi, Zayyadi; Herjuno, Dimas; Sari, Dwi Puspita (Universitas Islam Negeri Raden Intan Lampung, 2022)
In the process of documenting files for academic quality assurance and human resources recruitment, it is still conventional where there is still a physical accumulation of files, so that it can slow down the search for files or data needed, and can result in the risk of losing important data. In addition, the unavailability of a Human Resources (HR) recruitment information system that can facilitate prospective applicants for lecturers and staff The method of system development used in this study is the Structured Systems Analysis and Design (SSAD) Methodology. This methodology has several important stages that must be carried out in designing and building E-Dokument in the IIB Darmajaya Information Systems study program With the existence of a mobile-based quality assurance e-document system, it is hoped that it can assist the department in documenting quality assurance files. This system can be accessed by the KBK department, the department secretary and the head of the department of all str level study programs